Proinflammatory S100 proteins as clinical markers of juvenile idiopathic arthritis - Rusonienė, Skirmantė; Panavienė, Violeta; Eidukaitė, Audronė; Jakutovič, Marija (Acta medica Lituanica, 2014)
Objectives. Proteins of the S100 family (S100A8/9, or calprotectin) are known to be useful diasease activity biomarkers of JIA. We hypothesize that titres calprotectin in serum and synovial fluid of children with acute and unconfirmed inflammatory joint symptoms will identify patients who will progress to JIA and our aim is to examine its prognostic value. Methods. A standardized diagnostic evaluation and analysis of serum S100A8/A9 was performed in 115 children with acute (symptoms up to 6 weeks) arthritis as well as in 59 healthy individuals. 47 arthritis patients underwent joint fluid aspiration and samples were collected at the time of presentation. Proteins in serum and synovial fluid were measured by ELISA and compared by the unpaired t test. Arthritis outcome (chronic or transient arthritis) was recorded at 1- and 2-year follow-up periods. JIA diagnosis, disease activity and remission were established according to ILAR and ACR recommendations. Results. The levels of serum and synovial fluid S100A8/A9 were significantly higher in patients with arthritis compared to the levels in healthy individuals (p
Keywords: juvenile idiopathic arthritis; S100 proteins; calprotectin; serum and synovial fluid; outcome; predictors